A novel fast MPPT strategy used for grid-connected residential PV system applied in morocco - Sana Sahbani; Hassane Mahmoudi; Abdennebi Hasnaoui; Mustapha Kchikach; Hanane Benchraa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Regardless its significant potential for generating renewable energy, Moroccan government prohibited the injection of production surplus into the low voltage (LV) network because it still lack the implementing decreases, that represents one of the principal challenges for residential self-production in the country. The focus of this paper work is to introduce and analyze a novel fast MPPT strategy applied in an improved grid-connected Residential PV system respecting the current legislative framework in Morocco, which allow to the consumer being an actor in the energy transition towards a low-carbon society by reducing his dependence to the electrical grid and managing his own energy consumption efficiently by a good switching between photovoltaic (PV) source and the grid and therefore making a framework of smart residence management system. The overall system is designed to improve the energy control performance with two techniques: the first one uses a novel high performance controller to track the maximum power point (MPP) of a photovoltaic array under fast irradiation and load changes. Among the advantages of this proposed controller is the stability of its output voltage with fast response speed to the required parameters. The second one uses a Power Factor Correction (PFC) circuit to ensure the power quality regulation in the grid side via a predictive current control method. Finally, the stability of a closed-loop system is simulated and analyzed using commercial software offering sufficient conditions to validate a practical stability and robustness of the proposed overall designed system.